Prevalence of coccidial infections in the West African Dwarf goat in the subhumid zone of Nigeria - Woji, A.Y.; Little, D.A.; Ikwuegbu, O.A. (Springer, 1994)
An investigation was made of the seasonal incidence of coccidial infeciton in West African Dwarf (WAD) goats in 2 villages and an on-station situation in the subhumid zone of Nigeria. Faecal samples were obtained from about 70 goats in each village and 160 on-station at 4 times of the year, early and late dry and wet seasons. Six species of Eimeria were found to occur; E. arloingi, E. apsheronica, E. palida, E. alijevi, E. jolchievi and E. ninakohlyakimovae which accounted for 18, 16, 2, 9, 24 and 11 percent of infections respectively. Overall rates of infection were very high, averaging apporximately 87 percent, and peaked during the late wet season, when the proportion of heavy infections also increased significantly. At this time the proportion of infections classified as heavy was significantly higher in the village goats than the on-station goats, and was also significantly higher in kids than in adults. Clinical disease only occured in kids. The potential benefits of controlling such infections in terms of productivity responses appear worthy of further investigation in these farming systems.